Urokinase receptor is a multifunctional protein: influence of receptor occupancy on macrophage gene expression. - Rao, N K (1995)
Binding of urokinase to the glycolipid-anchored urokinase receptor (uPAR) has been implicated in macrophage differentiation. However, no biochemical markers of differentiation have yet been directly linked to uPAR occupancy. As extensive changes in proteolytic profile characterize monocytic differentiation, we have examined the role of uPAR occupancy on protease expression by differentiating phagocytes. Antibodies to either urokinase or to uPAR that prevent receptor binding inhibited induction of cathepsin B in cultured monocytes and both cathepsin B and 92-kD gelatinase mRNA and protein in phorbol diester-stimulated myeloid cells. Mannosamine, an inhibitor of glycolipid anchor assembly, also blocked protease expression. Anti-catalytic urokinase antibodies, excess inactive urokinase, or aprotinin had no effect, indicating that receptor occupancy per se regulated protease expression. Antibodies to the integrins CD11a and CD29 or to the glycolipid-anchored proteins CD14 and CD55 also had no effect. Protease induction was independent of matrix attachment. Antibodies to urokinase or uPAR affected neither the decrease in cathepsin G nor the increase in tumor necrosis factor-alpha in phorbol ester-stimulated cells. These data establish that uPAR is a multifunctional receptor, not only promoting pericellular proteolysis and matrix attachment, but also effecting cysteine- and metallo-protease expression during macrophage differentiation.